High-resolution timing observations of Spin-Powered Pulsars with the AGILE Gamma-Ray Telescope - Pellizzoni, A.; Pilia, M.; Possenti, A.; Fornari, F.; Caraveo, P.; Hotan, Aidan (The American Astronomical Society, 2009)
Italian Space Agency dedicated to high-energy astrophysics launched in 2007 April. Its~1 us absolute time tagging capability coupled with a good sensitivity in the 30MeV-30 GeV range, with simultaneous X-ray monitoring in the18-60 keV band, makes it perfectly suited for the study of gamma-ray pulsars following up on the Compton Gamma Ray Observatory/EGRET heritage. In this paper, we present the first AGILE timing results on the known gamma-raypulsars Vela, Crab, Geminga, and B1706-44. The data were collected from 2007 July to 2008 April, exploiting the mission Science Verification Phase, the Instrument Timing Calibration, and the early Observing Pointing Program. Thanks to its large field of view, AGILE collected a large number of gamma-ray photons from these pulsars(~ 10,000 pulsed counts for Vela) in only few months of observations. The coupling of AGILE timing capabilities, simultaneous radio/X-ray monitoring, and new tools aimed at precise photon phasing, also exploiting timing noise correction, unveiled new interesting features at the submillisecond level in the pulsars' high-energy light curves.